Role of MicroRNAs in innate neuroprotection mechanisms due to preconditioning of the brain - Jimenez-Mateos, Eva M. (Frontiers in Neuroscience, 2015)
Insults to the brain that are sub-threshold for damage activate endogenous protective pathways, which can temporarily protect the brain against a subsequent harmful episode. This mechanism has been named as tolerance and its protective effects have been shown in experimental models of ischemia and epilepsy. The preconditioning-stimulus can be a short period of ischemia or mild seizures induced by low doses of convulsant drugs. Gene-array profiling has shown that both ischemic and epileptic tolerance feature large-scale gene down-regulation but the mechanism are unknown. MicroRNAs are a class of small non-coding RNAs of 20–22 nucleotides length which regulate gene expression at a post-transcriptional level via mRNA degradation or inhibition of protein translation. MicroRNAs have been shown to be regulated after non-harmful and harmful stimuli in the brain and to contribute to neuroprotective mechanisms. This review focuses on the role of microRNAs in the development of tolerance following ischemic or epileptic preconditioning.